Effects of exercise interventions on cognitive function in patients with cognitive dysfunction: an umbrella review of meta-analyses - Sun, Guangyao; Ding, Xingyi; Zheng, Zhong; Ma, Hongtao (Frontiers in Aging Neuroscience, 2025)
ObjectiveThis umbrella review assessed the quality, potential biases, and effects of exercise interventions on cognitive function in individuals with cognitive impairments.MethodsA comprehensive umbrella review of meta-analyses of randomized controlled trials (RCTs) was performed to evaluate the effects of exercise on cognitive function in individuals with cognitive impairments. Databases including Web of Science, PubMed, Embase, and the Cochrane Database of Systematic Reviews were searched. Outcomes were evaluated using the Grading of Recommendations, Assessment, Development and Evaluation (GRADE) system, classified as “high,” “moderate,” “low,” or “very low” quality.ResultsA total of 55 meta-analyses were included, covering dementia, cognitive impairment, MCI, Alzheimer’s disease (AD), Parkinson’s disease (PD), and stroke. Cognitive outcomes were assessed using scales like MMSE and MoCA. High-quality evidence supports Exergaming (SMD 0.69), Tai Chi (SMD 0.36), and traditional Chinese mind–body exercises (SMD 0.32) for improving MMSE and MoCA Score in MCI patients. For dementia, moderate-quality evidence shows resistance training (SMD 0.60) and Tai Chi (SMD 0.27) have positive effects. Aerobic exercise (MD 2.95) was more effective for AD, while mind–body exercises (MD 1.68) benefitted PD patients. Multi-component exercises (SMD 0.67) improved MMSE and MoCA scores in post-stroke cognitive impairment. For unspecified cognitive impairments, combining exercise with cognitive training and traditional Chinese exercises showed higher effectiveness. Due to small sample sizes, all findings were Class IV evidence, requiring further research.ConclusionModerate to high-quality evidence supports Exergaming, Tai Chi, and traditional Chinese exercises in improving cognitive function in MCI. For dementia, resistance training and Tai Chi are effective; for AD, aerobic exercise; for PD, mind–body exercises; and for post-stroke cognitive impairment, multi-component exercises are beneficial.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/view/CRD42024587635, identifier [CRD42024587635].